Prevention 1st by state mandate - Health promotion as an overarching educational goal and teaching principle in primary school curricula: A comparison between Austria, Germany and Switzerland - Katharina C. Wirnitzer; Isabella Troppe; Derrick R. Tanous (Bern Open Publishing, 2024)
Introduction & Purpose Health is a basic prerequisite in leading a fulfilled life; thus, it is one of the major topics of our time. In line with the United Nations Sustainable Development Goals (UN SDG's), especially Goals #3 "Good Health and Well-Being" and #4 "Quality Education" (United Nations Department of Economic and Social Affairs, 2022), the link between health and education is emerging as a focal point for the future of mankind. According to the World Health Organization (WHO; 2023), non-communicable diseases (NCDs) like cardio-vascular disease, cancer, or diabetes type 2 cause 74% of all deaths worldwide; the main risk factors promoting NCD development include unhealthy lifestyles, such as insufficient physical activity (PA) and/or poor dietary patterns. According to the WHO Health Behaviour of School-aged Children study, only 19% of all girls and boys in Europe and Canada meet the WHO's physical activity recommendations (at least 60 min/day; WHO 2020). In addition, 1 in 5 adolescents are overweight/obese, and the diet of most adolescents does not meet current recommendations (Inchley et al., 2020). Since exercise and food are each considered medicine, regular PA & exercise permanently linked to a healthy diet serves as the most promising and basic dual approach to sustainable and lifelong health from childhood into old age. Given that lifestyles (for better or worse) and inherited habits track from childhood to old age, the power of informed lifestyle choices shall be applied early in life to prevent people from developing NCDs and their risk factors, rather than being applied to patients and in old age. Children are considered the future and are therefore key drivers of a global shift towards healthier and more sustainable lifestyles. Considering that children and adolescents spend a significant amount of their wake and activity time in formal educational settings, the school environment is key in learning, understanding, applying and implementing health-related knowledge as well as promoting healthy behaviors. Compulsory school time covers 9 years for Austrian pupils, while European children have to attend school over a range of compulsory schooling of 8-13 years. Therefore, schools are ideal places to implement health-promoting measures. The aim of this study was to systematically (quantitatively) and contextually (qualitatively) review and compare the primary school curricula of the DACH (D-Germany; A-Austria; CH-Switzerland) region for the first time regarding a 1-dimensional versus a dual health approach in the context of PA & exercise and/or nutrition. This contribution (1) further identifies the remaining gaps between schools and university/college education and training for future development and (2) spans from the gap between the curricular state mandate and the huge potential of school health promotion for better public health left untapped so far by providing potential hands-on solutions in order to contribute to addressing today's health paradox. The contribution is related to the German-language publication (Troppe et al. 2024). Methods A (quantitative) systematic review with contextual-qualitative fractions and a comparative analysis of the primary school level curricula of the German-speaking DACH region was conducted (01-12/2023); however, representative for the 16 federal states all over Germany the Bavarian curriculum was selected as best match for socio-cultural and geographical characteristics. Within 4 specific umbrella term-categories (a - PA & exercise; b - nutrition; c - health; d - sustainability), related keywords were searched for in the respective documents. The basic data or hits were processed by using a didactical tool with distinct inclusion and exclusion criteria ("Ampelsystem"; Troppe et al. 2024). By applying this matrix, the basic data were refined one step at a time (number of hits, quantitative matches, qualitative matches via contextual verification) with the results matching from red over yellow to green categorization. Results (1) All primary school curricula analyzed for the DACH region include a 1-dimensional health approach with a main focus on the lifestyle factor PA & exercise (N = 1,050). In addition, the entrenchment of health and health promotion in all the DACH curricula was predominantly found in the compulsory subject Physical Education, which contains the majority of results (range: 116-346 or 42-82%), with 89-93% of the subject's matches identified within the search category PA & exercise. (2) Health as a category total (N = 177) ranks second, followed by Sustainability ranked top-3 (N = 119), while the search category nutrition was found in the last rank with the least keyword matches found for the green results category (N = 38; Figure 1). (3) Only the German primary school curriculum contains at least one mention regarding a dual health approach. Discussion The most important finding of this study is that by state mandate, the compulsory subject Physical Education backed up by PA & exercise terminology is in the lead for health promotion and health literacy based on the primary school curricula of the DACH region. Far ahead, this subject interestingly outperformed more closely related health terminology, such as health, sustainability, or even nutrition, which is not often prioritized in any of the curricula. With regard to a dual approach to sustainable health, the DACH primary level curricula mentions only one single provision (respectively in the German curriculum for the subject Heimat- und Sachunterricht), with one specific wording identified with a clear formulation considering the dual approach to sustainable health: "The pupils ... explain the connection between nutrition, leisure time behaviour, exercise, well-being and health". This evidence underlines not only that there is a huge potential left to be tapped for improving Child Public Health and thus better future Public Health, but also that school health promotion is under the lead of Physical Education and, as by state mandate, defined at the center of a sustainable teaching-learning process. Health promotion - starting with PA & exercise - is therefore relevant to implement at all compulsory school subjects by competence- and action-oriented measures. Due to the great potential identified for school health promotion for the prevention of NCDs (cf. Child Public Health) and better future Public Health of nations like Austria, further research seems necessary. Practical implications/future perspectives The contribution of any single individual to positively influence one's own health - and to improve public health as a result - is enormous, but insufficient on its own. This underlines the urgency of prioritizing the educational goal of health promotion/education at national, international, and global levels. In view of the impending consequences, all political and educational actors must work together to safeguard human health. At the same time, however, there still remain gaps to overcome by policy and decision makers in governmental and educational settings and levels. One such central gap is the lack of systematic (basic and advanced) education and training by standard tertiary curricula of future teachers and doctors with health-related qualifications and empowerment considering the power of lifestyle. With the promising dual approach as a minimum recommendation (still left to be addressed), the next generation of teachers, doctors and health professionals will qualify to fulfill the curricular state mandate of health promotion in any single compulsory school subject. Health promotion and health education must therefore be used as a central measure (interdisciplinary educational goal) since entrenched in the Austrian curricula in order to act in an evidence-based manner concerning sustainable development. Potential approaches for much needed change include: (1) appropriate educational measures regarding the enormous benefits of lifestyle medicine emerging from 6 interwoven areas on a curricular basis, in particular (a) teaching from primary to upper secondary level, (b) basic, further, and advanced training at universities/colleges (medicine, health professions, teaching/education, etc.), and (2) communal catering (university, hospital, retirement home, etc.).